Noncommunicable diseases among school-going adolescents: A case study on prevalence of risk factors from Sabarkantha District of Gujarat, India - Tapasvi Puwar; Deepak Saxena; Sandul Yasobant; Shital Savaliya (Wolters Kluwer Medknow Publications, 2018)
Background: The increasing burden of noncommunicable diseases (NCDs) and large proportion of adolescent population in India; crafts the dynamics of NCD risk factors. Most of the NCD risk factors are behaviorally acquired which are due to change in lifestyle during adolescent age groups. Objective: This study aims to determine the prevalence of risk factors among school-going adolescents in one of district of Gujarat state, India. Subjects and Methods: This is a cross-sectional study conducted among sampled schools of Sabarkantha district of Gujarat, India, during September-December 2016. A total of 484 school-going adolescents were screened for body weight, height, blood pressure, and some information of sociodemographic, lifestyle habits, and family history were collected through a structured questionnaire in vernacular language. Data were managed with SPSS version 20. Results: This study documents that not having fruits and not doing physical activities daily are the major risk factors of NCDs among school-going adolescents of Sabarkantha district, Gujarat. In addition to this, also it has been documented that there are differential standards for body mass index (BMI) available for adolescents and have been used extensively in various studies. This study provides an insight to these three major BMI standards and their differences in measurement for the school-going adolescents. Conclusions: This study recommends promoting healthier practices for prevention of NCD lifestyle risk factors among school-going adolescents and it also recommends standardizing the BMI measurements for adolescents for India.